Blacklists and whitelists in the framework of a domain reputation system - Cristian-Alexandru GHEORGHIȚĂ; Dragoș SMADA; Adrian-Victor VEVERA; Mihail DUMITRACHE; Ionuț-Eugen SANDU; Carmen-Ionela ROTUNĂ (Revista Română de Informatică și Automatică, 2023)
The current research approaches the implementation of a real-time domains monitoring platform to determine their reputation, which involves data collection, machine learning analysis, and creating a realtime monitoring interface. Collaboration between various parties and continuous platform improvement are essential to meet evolving user needs and cybersecurity demands. This integrated approach strives to ensure a safer online environment by monitoring and enhancing the reputation of internet domains. The purpose of a domain name reputation system is to assess the trustworthiness of internet domain names. It relies on key components like whitelists, blacklists, registry data and domain rating tools for evaluation and security. Requirements for developing a domain name reputation system highlights the essential prerequisites for an effective domain name reputation system. A significant emphasis is placed on the identification and use of blacklists and whitelists to distinguish trusted from untrusted domains.